(untitled) (Jagannath University Journal of Life and Earth Sciences, 2024)
Selfie is an interesting self-portrait phenomenon that has changed young people’s communication and leisure time. Instead of living in the present moment, people are busy clicking selfies and uploading them on social media, adversely impacting their psychological health. Thus, the present study was designed to explore the impact of selfitis behavior on psychological distress among students at various educational levels (i.e., schools, colleges, and universities). Data were collected purposively from 400 participants at different educational institutions situated in Dhaka city. A package of Bangla-adapted versions (Zaman and Konica, 2019) of measuring tools (i.e., selfitis behavior scale and psychological distress scale) and a personal information form were used to collect the necessary information regarding the study. Results revealed that selfitis behavior was positively correlated with psychological distress. The individual effect of selfitis behavior construct identified two significant predictors (i.e., environmental enhancement and attention seeking), which jointly explained 12.6% of the variance in psychological distress. Here, the strongest predictor of psychological distress was attention-seeking, which alone explained 10.3% of the variance in psychological distress. Further, results also revealed that the three significant demographic predictors (i.e., socioeconomic status, daily selfie-taking, and educational qualification) jointly explained 16.1% of the variance in psychological distress. These results suggest valuable insights for researchers, educators, and educational counselors dealing with these concerns. Additionally, the findings would aid psychologists, parents, teachers, and other stakeholders in comprehending the factors contributing to psychological distress. Jagannath University Journal of Life and Earth Sciences, 9(2): 133-146, 2023 (December)